PENGUASAAN KONSEP, BERPIKIR KRITIS, DAN BERPIKIR KREATIF PADA MATA KULIAH BIOLOGI SEL DENGAN MENGGUNAKAN MULTIMEDIA ANIMASI DI PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UMB - Nurul Abidin (DINAMIS, 2017)
This study aims to determine differences in the mastery of concepts, critical thinking, creative and cell biology of the students who get the cell biology of learning using multimedia animation with students who do not get the cell biology of learning with multimedia animation.while also, this study aims to determine the correlation between mastery of concepts, ability to think critically and creatively in the experimental class and control. The research was conducted at the Muhammadiyah University of Bengkulu in February and March 2012, with research subjects is the second semester of biology education students who took the course. As this study used a quasi-experimental posttest-only control group design, with a group / class as the control class and one group / other class as a whole class of experiments with the number of students is 59 people. Treatment given the form of cell biology-based learning by combining a variety of multimedia digital media whether text, graphics, images, animations, video, or sound made in a medium of learning to use the software version of Microsoft Power Point ® 2007 and Macromedia Flash 8 Professional. Based on the results of the study. Data were analyzed with the test for normality, homogeneity test, t test, and Kendall's tau correlation test-b and Spearman's rho. Based on data analysis known that the class get the cell biology of learning using multimedia animation has a mastery of the concept (PK) cell biology that are not significantly different between the students in the experimental class and control class. Of the results is also known that the critical thinking skills (BKi) among students in the experimental classes and control classes are not significantly different. Meanwhile, the ability to think creatively (BKe) between the experimental class and control class there is a difference, where the class control has the ability to think creatively on average higher than the experimental class. The results of correlation analysis showed a weaker correlation between PK with BKe in class experiments, and experiments in the classroom there is a strong correlation between PK with BKi.